Self-efficacy, reflection, and resilience as predictors of work engagement among English teachers - Heng, Qingzhi; Chu, Lina (Frontiers in Psychology, 2023)
Introduction Given the significant role of work engagement of teachers in educational contexts, some scholarly attention has been directed to exploring the predictors of this construct. Against this backdrop, this study aimed to investigate the predictors of teacher work engagement among Chinese English as a foreign language (EFL) teachers by testing a model that includes teacher self-efficacy, teacher reflection, and teacher resilience. Methods To achieve this goal, 512 EFL teachers were invited to participate in an online survey, which consisted of four questionnaires. The construct validity of the measures was confirmed through confirmatory factor analysis. Then, structural equation modeling was utilized to examine the relationships between the variables. Results The findings indicated that teacher self-efficacy, teacher reflection, and teacher resilience were direct predictors of work engagement, and teacher self-efficacy had an indirect effect on work engagement via teacher reflection and resilience. Similarly, teacher reflection also had an indirect impact on work engagement through teacher resilience. Discussion These results have important implications for teacher education programs. The significance of these predictors of work engagement among EFL teachers highlights the importance of fostering self-efficacy, reflection, and resilience among teachers in order to promote their work engagement. Further research can explore ways to enhance these predictors through training and support programs for teachers.